2001
DOI: 10.1590/s0004-28032001000100005
|View full text |Cite
|
Sign up to set email alerts
|

Hipertensão portal por esquistossomose mansônica hepatoesplênica: efeito da desconexão ázigo-portal com esplenectomia no diâmetro e na velocidade média de fluxo do sistema portal (estudo ultra-sonográfico com Doppler)

Abstract: (10,6 ± 2,9, 8,0 ± 1,8, 9,1 ± 2,6 cm); a velocidade média de fluxo na veia porta e nos ramos portais foi semelhante (15,62 ± 6,17, 14,92 ± 5,33, 16,12 ± 4,18 cm/seg). No grupo B (operados): houve diminuição de ambos os parâmetros na veia porta e seus ramos (8,8 ± 1,7, 5,2 ± 1,2, 7,5 ± 2,2 cm/12,53 ± 2,60, 8,86 ± 1,75, 9,60 ± 3,75 cm/seg

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
2
6
0
2
Order By: Relevance
“…This study, with a mean follow-up higher than 10 years, showed that all patients had a significant reduction of their variceal size, in accordance of previous reported results with short 21 and long term follow-up 14 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study, with a mean follow-up higher than 10 years, showed that all patients had a significant reduction of their variceal size, in accordance of previous reported results with short 21 and long term follow-up 14 .…”
Section: Discussionsupporting
confidence: 92%
“…Studies have shown that gastrointestinal bleeding due to rupture of esophageal varices occur in 40% ¹ and it is the most threat to survival in patients with hepatosplenic schistosomiasis ²¹ with a mortality rate of 11.7% in the first episode of bleeding 12 . The importance of this disease regarding public health was demonstrated by a survey from the Ministry of Health between 1998 and 2009 that showed an annual mortality rate estimated to be between 0.2 and 0.34 deaths per 100.000 inhabitants ²³ .…”
Section: Introductionmentioning
confidence: 99%
“…WIDMAN et al (39) demonstraram, por análise ultra-sonográfica, que há redução significativa no calibre da veia porta em pacientes operados por DAPE em relação a pacientes não-operados acometidos da forma hepatoesplênica da esquistossomose. Não obstante, relacionaram essa diminuição do calibre no pós-operatório à diminuição da pressão do FP.…”
Section: Discussionunclassified
“…Também deve ser considerada a lesão endotelial causada pela secção e ligadura da veia esplênica 9 . A desconexão ázigo-portal com esplenectomia determina a redução do calibre da veia porta e a diminuição do índice portal hepático, caracterizando uma redução do componente de hiperfluxo portal 22,23 . A ultra-sonografia com doppler tornou-se o método de escolha para a avaliação do sistema portal por não ser invasiva, possuir baixo custo, ser rápida e reprodutível e possuir grande acurácia em estabelecer o diagnóstico de hipertensão portal.…”
Section: Discussionunclassified